Study on the QPQ Treatment Process for Surface of 05Cr17Ni4Cu4Nb Material - LI Duan, WANG Bei, WU Di, ZHANG Bo (Cailiao Baohu, 2021)
In order to improve the wear resistance of 05Cr17Ni4Cu4Nb material, extend the service life and expand the application, the surface of 05Cr17Ni4Cu4Nb stainless steel was strengthened by QPQ heat treatment process.The influence of the different nitriding time and cyanate ion concentration in base salt on the thickness and hardness of the surface nitriding layer were studied by scanning electron microscope and harder tester.Results showed for 05Cr17Ni4Cu4Nb stainless steel rods, when the concentration of cyanide was 32%～35% or 35%～38%, and the nitriding time was 30～40 min or 35～45 min, respectively, the thickness of nitriding layer on the material surface could reach 20～30 μm.For 05Cr17Ni4Cu4Nb stainless steel plates, when the concentration of cyanide was 32%～38%, and the nitriding time was 20～30 min, the thickness of nitriding layer on the material surface could reach 20～30 μm.Moreover, the optimized QPQ heat treatment process had a certain guiding role for the practical application of 05Cr17Ni4Cu4Nb stainless steel.